Understanding the Sustainability of Selected Recommendations for a Nursing Best Practice Guideline within an Acute Care Context - Nadalin Penno, Letitia (Université d'Ottawa / University of Ottawa, 2021)
Background: To date, little attention has focused on what the factors are and how Best Practice Guidelines (BPGs) are sustained in acute care over time. Problem: For ten years, a multi-site acute care center supported the use of a Pain Assessment and Management Policy and Protocol (Pain P/P), placing the decision to use it with point of care nurses. Despite early implementation success, the nursing department identified an evidence-based gap on Medicine care units. Purpose: To (i) identify factors influencing nurses’ use (or not) of the Pain P/P over time, and ten years post-implementation; (ii) examine related knowledge translation interventions (KTIs) used over time, and ten years post-implementation; (iii) validate unit nurses’ use of the Pain P/P ten years post-implementation; and (iv) identify relevant sustainability frameworks/models/theories (F/M/Ts), constructs and factors for sustained use of BPGs in acute care. Methodology: A case study of an organization-wide nursing BPG was conducted ten years following initial implementation using mixed methods guided by the Dynamic Sustainability Framework (Chambers, 2013). The case study setting was a 1122 bed acute care center in Canada. I examined BPG sustainability at the (corporate) department and unit levels (two embedded subcases). Data sources included 19 informant interviews (3-corporate, 16-unit level), 200 chart audits (100/subcase), and 29 documents. I concurrently conducted a systematic review to identify sustainability concepts and factors for use in acute care to compare case study results. Results: I identified 7 constructs, 49 factors, and 29 KTIs influencing sustained use of evidence-base practices (EBPs) in acute care. Three factors and eight KTIs had a continuous influence during implementation and sustained use phases. Findings confirm the concept of sustainability is a dynamic ‘process’ or ‘ongoing phase’. Conclusions: This thesis provides a novel resource to support future practice and research aimed at sustaining EBPs to improve nursing practice and related patient outcomes. Attention to the level of application and changing conditions over time impacting factors that influence EBP use is required for sustainment. Use of a participatory approach to engage users in designing remedial plans and link KTIs to target behaviors that incrementally address low adherence rates promotes sustainability.
Keywords: sustainability/sustainment; frameworks/models/theories; routinization; institutionalization; adherence; audit; quality improvement; case study; nursing; evidence-based practices/guidelines/programs/interventions/innovations